PENGARUH MOTIVASI, DISIPLIN KERJA DAN KOMITMEN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM KABUPATEN GOWA - Basalamah, Jafar (Universitas Indo Global Mandiri Palembang, 2020)
This study aimed to determine whether there is a real and significant effect Motivation, Work dicipline and Work commitment, together on the performance of officer at Gowa district public works and determine which variables are the most dominant influence on the performance of officer at Gowa district public works. The method used is descriptive method. Collecting data using a questionnaire filled out by the respondent, then analyzed using multiple linear regression analysis.The results showed that the variable motivation (X1), Variable work dicipline (X2) and Variable work commitment (X3) Simultaneously significant effect on the performance of officer at Gowa district public works. The variables that have the most significant effect on the performance of officer at Gowa district public works is variable motivation (X1).Keywords : Motivation, Work Dicipline, Commitment, and Employee Perfomance